303-OR: Notch Signaling Inhibitor ADPO-002 Promotes Browning in Human Adipose Tissue Explants - RAISUL ABEDIN, MUHAMMAD; FREIJE, WILSON; OSWALT, MALLORY A.; ACTON, ANTHONY J.; CRAWFORD, CHRISTOPHER B.; INMAN, MARGARET M.; CONSIDINE, ROBERT V.; DENG, MENG (Diabetes (New York, N.Y.), 2024)
Introduction: Transformation of white adipocytes into beige adipocytes, known as adipocyte browning, holds great promise for development of new therapeutics. Our previous studies have demonstrated nanoparticle-based delivery of dibenzazepine (ADPO-002), a γ-secretase inhibitor, induces browning of white adipose tissue in obese mice and in pigs. The current study aims to investigate the browning efficacy of ADPO-002 in human adipose tissue organ culture. Methods: Abdominal subcutaneous and omental adipose tissue samples were collected from 24 subjects undergoing bariatric surgery (BMI 47.5±3.2 kg/m2, age 44.8±3.0 yr). The study was approved by the Ascension St. Vincent hospital IRB and all subjects provided informed consent. Tissues were cut into small pieces (~5-10 mg) using surgical scissors and cultured in medium M199 supplemented with 0.7 nM insulin and 10 nM dexamethasone. The treatment groups were DMSO (negative control), 50 µM forskolin (positive control), and 3, 10 and 30 µM ADPO-002. After 7-days treatment, total RNA was isolated, and RT-qPCR performed for the browning marker genes PRDM16 and PGC1A. Statistical significance was determined using Wilcoxon non-parametric paired t-test. Results: In omental adipose tissue, 30 µM ADPO-002 significantly increased PRDM16 (429.1±149.3 vs 10.6±4.9 relative units, p=0.0020) and PGC1A (117.4±58.7 vs 58.5±30.2 relative units, p=0.0273) expression compared to the control group. In subcutaneous adipose tissue, 30 µM ADPO-002 significantly upregulated PRDM16 expression compared to control group (398.9±198.6 vs 22.06±6.28 relative units, p=0.0039). Conclusion: These findings suggest that ADPO-002 treatment increases the expression of genes associated with increased mitochondrial expression. This finding supports the hypothesis that inhibition of γ-secretase can increase browning in human adipose tissue.